6700 years of diatom changes related to land use and climatic fluctuations in the Lake Aydat catchment (Auvergne, France): Coupling with cyanobacteria akinetes, pollen and non-pollen palynomorphs data. (30th October 2022) - Beauger, Aude; Serieyssol, Karen; Legrand, Benjamin; Latour, Delphine; Berthon, Vincent; Lavrieux, Marlène; Miras, Yannick
Abstract: Nowadays Lake Aydat is an important site for tourism activities but blooms of cyanobacteria induced some restriction for aquatic activities by humans and their livestock. Thus, it was important to understand the lake's history as it should help in the development of restoration strategies to improve water quality in the future. Lake Aydat had a complex history affected by climatic changes and human influences. Two different sedimentary periods of deposition were observed (6700 ± 200–3180 ± 90, and 1770 ± 60 cal. BP – nowadays) separated by a mass wasting deposit. The lower unit was dominated by Stephanodiscus diatom species ( S. medius, S. minutulus and S. parvus ) and two Aulacoseira species ( A. pusilla and A. subarctica ) and the upper layer by Aulacoseira subarctica and its form recta along with Lindavia radiosa and a series of "Fragilariod" taxa. The eutrophic diatom species increase, associated with the lower layer, was most likely related to prehistorical human activities within the watershed (progressive change from a wooded landscape to an agricultural patchy landscape). The Middle Bronze Age degradation was noted as a period with a rise in planktonic and tychoplanktonic diatom species. The lower diatom zone in the upper unit marked the final transition to a domination of agricultural practices and high human pressure and a whole new set of environmental factors affecting the lake since 1750 cal. BP. Increased nutrient enrichment was observed and the Lindavia radiosa presence in the lake was associated with the beginning of hemp ( Cannabis sativa ) cultivation and an increase in agricultural pressure. High concentrations of cyanobacteria akinetes were associated with the final transition and the maximum of hemp cultivation, when the lake became very eutrophic. For future restoration strategies, improving the water quality will be a challenge as high concentrations of akinetes and nutrients are observed since the Antiquity in the lake.